Gender Mainstreaming in Urban Planning: The Potential of Geographic Information Systems and Open Data Sources. (15th March 2019) - Carpio-Pinedo, Jose; De Gregorio Hurtado, Sonia; Sánchez De Madariaga, Inés
ABSTRACT: While gender mainstreaming has become a key principle for fostering equality across all fields of policy, actual implementation in the field of urban planning is still underdeveloped. We posit that Geographic Information Systems (GIS) and open data sources can and should be useful tools that effectively contribute to devising more effective ways of implementing a gender-sensitive agenda in urban planning. We take the case of Madrid to illustrate how these tools can contribute to gender mainstreaming in planning by building a methodology based on the concepts of infrastructures for everyday life and the perception of safety.